The two sides of the coin. Stories of the Civil Post-War in Costa Rica - Ramírez Roldán, José David (2017)
The present paper aims to understand the life experiences of two male witnesses about events that occurred in the aftermath of the 1948 Civil War and Post-War in Costa Rica. It should be noted that the fact in question left them marked, in one way or another, for the rest of life in their personal development. The fisrt one, who lived the experience of war in his childhood as the son of a Communist leader killed in the Codo del Diablo early in the postwar period at the hands of the Costa Rican State; and the second, witnessed these events during his adolescent time, in which he was a combatant of the “figuerista” side during the war. These stories were collected through two semi-structured interviews that were adequate for each particular case, with duration between half and one hour each, which were carried out in the first half of 2015. The research also offers a theoretical-methodological and contextual studies balance that was considered adequate as a way of historical analysis with respect to the testimonial sources used.